Commentary Gaudio D, Olivieri L, De Angelis D, Poppa P, Galassi A, Cattaneo C. Reliability of craniofacial superimposition using three-dimension skull model. J Forensic Sci 2016; 61(1):5–11 - Jayaprakash, Paul T.; Hadi, Helmi; Srinivasan, Alarmelmangai; Chellamuthu, Pushparani; Mohd Yusop, Ridzuan Abd Aziz; Hashim, Natassha (Wiley, 2016)
Sir, In a recent attempt to evaluate the reliability of the superimposition method using 3D laser scans of skulls and scanned face images, Gaudio et al. (1) reported 40 and 44.4% false positives for landmark and morphological methods, respectively, and concluded that their “study presents the validity of a different method of manipulation of the 3D model of the skull so that it can be more efficiently aligned with a 2D image.” The methods used by these authors include the placement of targets to indicate the landmarks in the skull and face images on screen and adjusting the transparency, size, and orientation of the images “to match orientation landmarks (i.e., right and left ectocanthion, subnasal point and nasion)” (1).